Bis-, Tris-, And Tetrakisbenzimidazolium Salts And Their Silver(I) Complexes: Synthesis, Characterization And Biological Applications - Abdurrahman, Nuraddeen (2024)
This research describes the synthesis, characterization, crystal structure and cytotoxicity activity of several new bis-, tris- and tetrakis-benzimidazolium salts, (1- 24) and their respective silver(I)-benzimidazol-2-ylidene complexes, (Ag1-Ag24). All the compounds synthesized were new based on literature reviewed, it was achieved by changing the either the alkyl or aryl substituents on the benzimidazolium systems and or the bridging ligands related to the previously reported compounds. The salts were synthesized by nucleophilic substitution reaction and were categorized into five series. The salts were 1-5, 6-9, 10-14, 15-19, 20-24 as first, second, third, fourth and fifth series respectively. The synthesized salts were utilized for the synthesis of their respective silver(I)-benzimidazol-2-ylidene complexes, by in-situ deprotonation method in the presence of silver(I)oxide. The cytotoxicity potential of the synthesized compounds was carried out by MTT assay method, in which the breast and cervical cancer cell lines were used. Salt 1-5, 6-9, 15-19, and their silver(I)-benzimidazol-2-ylidene complexes, (Ag1-Ag5, Ag6 -Ag9, Ag15-Ag19) were tested against breast cancer cell lines, while salts, 10-14, 20-24, and their silver(I)-benzimidazol-2-ylidene complexes, (Ag10-Ag14, Ag20-Ag24) were tested against cervical cancer cell lines. The positive control used for the breast cancer cell was tamoxifen and etoposide for the cervical cancer cell. All the salts and their respective silver(I)-benzimidazol-2-ylidene complexes synthesized were characterized using various characterization techniques including FTIR, 1H, 13C NMR, elemental analysis, and single crystal X-ray diffraction method. Physical properties were accessed by melting point analysis, and solubility tests in various organic solvents. From structural elucidation, it was confirmed that Ag2 was dinuclear silver(I)-benzimidazol-2-ylidene complex, with two PF6 anions as counterions balancing the charges of the entire molecule. Complex Ag13 confirmed to be a cylinder-like trinuclear silver(I)-benzimidazol-2-ylidene complex containing three silver(I) ions bridged by two disc-like ligands.